In vitro and in vivo biocompatibility and inflammation response of methacrylated and maleated hyaluronic acid for wound healing. Issue 53 (28th August 2020) - Zhang, Lijun; D'Amora, Ugo; Ronca, Alfredo; Li, Yuanyuan; Mo, Xiaoying; Zhou, Fei; Yuan, Mingzhou; Ambrosio, Luigi; Wu, Jun; Raucci, Maria Grazia
Abstract : From synthesis to the in vitro and in vivo biological evaluation of two types of hyaluronan derivatives. Abstract : Over the past few years, different in vitro and in vivo studies have been highlighting the great potentiality of hyaluronic acid (HA) as a biomaterial in wound healing treatment thanks to its good capability to induce mesenchymal and epithelial cell growth and differentiation, angiogenesis, and collagen deposition. However, the need to improve its mechanical properties as well as its residence time has led scientists to study new functionalization strategies. In this work, chemically modified HA-based hydrogels were obtained by methacrylic and maleic functionalization. Methacrylated (MEHA) and maleated HA (MAHA) hydrogels have shown important physico-chemical properties. The present study provides a deeper insight into the biocompatibility of both synthesized materials and their effects on tissue inflammation using in vitro and in vivo models. To this aim, different cell lines involved in wound healing, human dermal fibroblasts, human adipose-derived stem cells and human umbilical vein endothelial cells, were seeded on MEHA and MAHA hydrogels. Furthermore, an inflammation study was carried out on a murine macrophage cell line to assess the effects of both hydrogels on inflammatory and anti-inflammatory interleukin production. The results showed that both MAHA and MEHA supported cell proliferation with anti-inflammation ability as highlighted by the increased levels of IL-10 (57.92 ± 9.87 pg mL −1 and 68.08 ± 13.94 pg mL −1, for MEHA and MAHA, respectively). To investigate the inflammatory response at tissue/implant interfaces, an in vivo study was also performed by subcutaneous implantation of the materials in BALB/c mice for up to 28 days. In these analyses, no significant chronic inflammation reaction was demonstrated in either MEHA or MAHA in the long-term implantation.